ORGANIZATIONAL CHANGES AND THE IMPACT ON THE PERFORMANCE OF SHARIA BANK EMPLOYEES THROUGH AFFECTIVE COMMITMENT - muhammad zakiy; Pawestri Kinasih; Syarif As'ad (Universitas Airlangga, 2023)
Organizational changes in a company often bring significant impact. One of the impacts that may arise due to organizational changes is decreasing employee performance. In the Islamic banking industry in Indonesia, one of the banks that has made organizational changes is Bank Syariah Indonesia (BSI). For this reason, it is necessary to pay attention to strategies in dealing with these changes so that changes can run well. One way to improve employee performance is to increase employee affective commitment to the company. This study aims to determine the relationship of organizational change to employee performance mediated by affective commitment. Respondents in this study were employees of Bank Syariah Indonesia (BSI) who had worked before and after the merger. The data collection process was carried out online to 165 employees of Bank Syariah Indonesia (BSI) and then analyzed using the Structural Equation Modeling (SEM) method through the SmartPLS 3.2 application. This study proves that organizational change has a negative effect on affective commitment, while affective commitment has a positive effect on employee performance. In addition, this study also proves that affective commitment is able to mediate a negative relationship between organizational change and employee performance. Therefore, employees need to increase their affective commitment in order to improve performance so as to support organizational change.